Transformasi Pakan Ikan Berbasis Maggot untuk Mewujudkan Ekosistem Agro-Akuaseloka Sirkular di Desa Panti - Aprillianto, Bayu; Ammar, Naufal; Dewi, Reni Puspita; Kurniawan, Anggi; Salabillah, Nabila Dwiani; Manik, Ella Septiana; Sitiwani, Sitiwani; Fauziah, Alifiyah Rizqy; Mukaromah, Nur Laily; Ramadhani, Rafli (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2025)
This study aims to develop the Agro-Aquaseloka model as an integrated system linking agriculture, aquaculture, and organic waste management through a circular economy approach in Panti Village, Jember Regency. The research employed a mixed-methods design with a Community-Based Participatory Research (CBPR) framework, involving local communities as active partners in all phases. Results indicate that training in Black Soldier Fly (BSF) maggot cultivation enhanced participants’ technical skills in converting organic waste into fish feed and organic fertilizer. The program reduced fish feed costs by up to 50% and improved profitability with a benefit-cost ratio (R/C) exceeding 1.3. It also decreased household waste volume by around 20% and reduced open burning practices. The establishment of the “Aguaseloka Farmer Group” strengthened local institutions and program sustainability. The model effectively promotes rural green economy development and supports Sustainable Development Goals (SDGs 1, 2, 8, 12, and 13).